Extent and evaluation of critical infrastructure, the status of resilience and its future dimensions in South Asia. (January 2023) - Mukherjee, Mahua; Abhinay, Kumar; Rahman, Md. Munsur; Yangdhen, Sonam; Sen, Subir; Adhikari, Basanta Raj; Nianthi, Rekha; Sachdev, Sanya; Shaw, Rajib
Abstract: South Asian Region (SAR) is not only home to about 25% of the global population but also the site of many disasters, making it one of the most disaster-prone regions on the planet. The vulnerability of most of the population in the SAR can be due to the poor critical infrastructure in the region. The network of essential infrastructures like power supply, transportation systems, financial services, and administration that are crucial for the functioning of a society is called the Critical Infrastructure (CI). Appropriate interconnectedness and coordinated interdependencies of CI are essential for the smooth functioning of society, and any disruption in one or more of them could cause improper functioning of society. The prime objective of this study was to evaluate the CI's requirement, condition and status in five countries, namely Bangladesh, Bhutan, India, Nepal, and Sri Lanka. Experts from these five countries conducted a semi-structured review of the past and existing risks and the existing CI to find the future requirements and advancements in the CIs. It was found that the backbone of the CI is advancement in technology and innovations that require collaborative and innovative research and sharing of information and data within and with other nations. Highlights: The status and extent of Critical Infrastructures in the South Asia Region are examined through expert critical analysis. Countries of SAR lack comprehensive infrastructure risk management, resulting in huge damage to CIs due to disasters. Collaboration and data exchange on hazards, risks, and research developments to learn from each other are important. Balance of grey-blue-green infrastructure based on the local socio-economic conditions and ecosystem adds resilience to CI.